VISTA variables in the Via Lactea (VVV): Current status and first results - Saito, R. K. (2010)
VISTA Variables in the Vía Láctea (VVV) is a public ESO near-IR variability survey aimed at scanning the Milky Way Bulge and an adjacent section of the mid-plane. VVV observations started in October 2009 during ESO science verification. Regular observations for the first year of the survey have been conducted since February 2010 and will cover a total area of 520 square degrees in five passbands and five epochs. Here we address the first results obtained from the VVV Survey as well as the current status of the observations.